The difference that friends can make: A study on the transition to university for students with and without Attention Deficit/Hyperactivity Disorder (ADHD) - Cho, Carrie (Université Saint-Paul / Saint Paul University, 2026)
There is limited research on the importance of friendship quality for students with ADHD, and which friendship quality dimensions are most implicated. An online questionnaire was completed by 350 second- and third-year university students with and without ADHD that measured students’ adjustment to university, the quality of a close friendship at university, and ADHD symptomatology. Hierarchical regression analyses indicated that overall friendship quality predicted improved adjustment to university for students with and without ADHD. Individual friendship dimensions of stimulating companionship, help, intimacy, self-validation, emotional security, and reliable alliance predicted better adjustment to university for students with and without ADHD. ADHD symptomatology was not a moderator in the link between university adjustment and overall friendship quality. Using correlational analyses, it was found that for students with ADHD, the friendship dimensions of help, self-validation, and emotional security were related to increased university adjustment. For students without ADHD, the friendship dimensions of stimulating companionship, intimacy, reliable alliance, and self-validation were associated with better adjustment to university. Findings can support the advancement of research and inform potential differentiation of student interventions, resources, and services.
Keywords: friendship; transition to university; attention-deficit/hyperactivity disorder; university; ADHD; adjustment; friendship quality